Distribution of In Vitro Fermentation Ability of Lacto-N-Biose I, a Major Building Block of Human Milk Oligosaccharides, in Bifidobacterial Strains - Xiao, Jin-zhong (American Society for Microbiology (ASM), 2010)
This study investigated the potential utilization of lacto-N-biose I (LNB) by individual strains of bifidobacteria. LNB is a building block for the human milk oligosaccharides, which have been suggested to be a factor for selective growth of bifidobacteria. A total of 208 strains comprising 10 species and 4 subspecies were analyzed for the presence of the galacto-N-biose/lacto-N-biose I phosphorylase (GLNBP) gene (lnpA) and examined for growth when LNB was used as the sole carbohydrate source. While all strains of Bifidobacterium longum subsp. longum, B. longum subsp. infantis, B. breve, and B. bifidum were able to grow on LNB, none of the strains of B. adolescentis, B. catenulatum, B. dentium, B. angulatum, B. animalis subsp. lactis, and B. thermophilum showed any growth. In addition, some strains of B. pseudocatenulatum, B. animalis subsp. animalis, and B. pseudolongum exhibited the ability to utilize LNB. With the exception for B. pseudocatenulatum, the presence of lnpA coincided with LNB utilization in almost all strains. These results indicate that bifidobacterial species, which are the predominant species found in infant intestines, are potential utilizers of LNB. These findings support the hypothesis that GLNBP plays a key role in the colonization of bifidobacteria in the infant intestine.